Pembangunan Aplikasi Pemantauan Pengambilan Makanan dan Aktiviti Harian di Pusat Jagaan Kanak-Kanak Secara Atas Talian - Hafizuddin, Muhammad Haziq; Mohd Yusof, Munirah (Applied Information Technology And Computer Science, 2021)
The Application for Monitoring Food Intake and Daily Activities in Child Care Centers is an application to help and enable parents to monitor daily activities and control their children's food intake online. The application offers several modules such as being able to view the child's information, view the child's daily activity schedule, view the child's Body Mass Index (BMI) information and so on. Currently, the childcare center records all daily activities manually, that is, the teacher has to record daily activities in a notebook. Therefore, it is very time consuming to fill in the information one by one and there may be a problem of financial wastage to buy a lot of notebooks. Next, the way this project is developed is by using a structured approach and using agile methodology. The application is developed using Android Studio for application development for parents while teachers and administrators use a web -based system and use Phpmyadmin as a database. This application allows parents to update personal information, update the child's information and view the child's daily activity schedule. For parents the web system allows the teacher to add the child's information, enter daily activities and allows the teacher to make a calculation of the child's BMI. The administrator allows to register parents and teachers, update all available information and generate reports according to the selected monthly. With this application, it can help parents monitor daily activities and control their child's food intake online.